2011
DOI: 10.1021/je1013119
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Metal Chelates of Some Hydroxamic Acid Ligands

Abstract: The binaryÀligand complexes formed between acetohydroxamic acid (Aha) and benzohydroxamic acid (Bha) ligands and selected transition metals (Sc(III), Y(III), and La(III)) were investigated potentiometrically in aqueous solution at (25 ( 0.1) °C and I = 0.10 M NaCl to determine the protonation constants of the free ligands and stability constants of the binary complexes. The complexation model for each metalÀligand system was established from the potentiometric data using the software program BEST. The concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…For potentiometric titrations, we used the special glass vessel used in our earlier studies [34] with a double wall, with entries for combined glass electrode (Schott), nitrogen and base from the burette (TL 7000-M2/20 automatic titrator). The emf measurements were made with this automatic titrator.…”
Section: Potentiometric Equilibrium Measurementsmentioning
confidence: 99%
“…For potentiometric titrations, we used the special glass vessel used in our earlier studies [34] with a double wall, with entries for combined glass electrode (Schott), nitrogen and base from the burette (TL 7000-M2/20 automatic titrator). The emf measurements were made with this automatic titrator.…”
Section: Potentiometric Equilibrium Measurementsmentioning
confidence: 99%
“…The potentiometric titration reactions were measured with a personal computer (PC) system, as described previously [4]. The solutions were adjusted to an ionic strength of 0.1 M with KNO 3 in a 100 mL jacketed glass cell equipped with a magnetic stirrer, and a water bath was used to control the temperature to 25.0 ± 0.1 • C. A slight positive pressure of purified nitrogen was maintained in the titration cell in order to exclude oxygen and carbon dioxide from the reaction solutions.…”
Section: Potentiometric Measurementsmentioning
confidence: 99%
“…The results of those previous studies suggested that Sc(III) ion forms the most stable complexes in binary ligand system in aqueous solution. The complexes of Sc(III), Y(III), and La(III) formed in different ionic mediums have been the most adequate complexes to identify the coordination number and the structure of these complexes [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…La is even less inclined to form strong coordinate bonds than Sc [1]. The stability constants of a number of relevant 1:1, 1:2 and 1:3 metalsome oxygen and nitrogen donor ligands-complexes reflects this [2][3][4][5][6][7][8].This might be unexpected in view of the charge of +3 ions, but it is complexed with greater electropositivity which inhibits covalent contribution to their bonding. La, of course, shows these characteristics more clearly than Sc.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have investigated the complexes formed between oxygen and nitrogen donating ligands and metal ions of Sc, Y and La using potentiometric methods [5,6,8,9]. Complexes formed between 8-Hydroxyquinoline 5sulfonic acid and Sc, Y and La have also been investigated in 0,1 M potassium nitrate ionic medium at 25,0 ºC [7].…”
Section: Introductionmentioning
confidence: 99%